2020
DOI: 10.1016/j.apsoil.2019.103362
|View full text |Cite
|
Sign up to set email alerts
|

Plant-parasitic nematodes parasitizing saffron in Morocco: Structuring drivers and biological risk identification

Abstract: Plant-parasitic nematodes (PPN) are the most destructive of all plant pathogens. They are an economically important group of soil pathogens, causing significant annual damages of up to 25% of world crop production. Morocco is considered to be a highly productive country for the colorant/medicinal/spice saffron (Crocus sativus L.). Taliouine and Taznakht regions are the most productive areas of this valuable neutraceutical. Due to its metabolic profile, and growth forms, saffron is susceptible to many plant dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Recently, Mokrini et al [60] emphasized that organic matter was negatively correlated with PPN patterns in Saffron. This trend was recorded in the same cropping system by Benjlil et al [99]. Organic matter accumulation in soils causes a significant decrease in nematode abundance [105,106].…”
Section: Effect Of Soil Characteristics On Ppn Abundance In Moroccan supporting
confidence: 63%
See 1 more Smart Citation
“…Recently, Mokrini et al [60] emphasized that organic matter was negatively correlated with PPN patterns in Saffron. This trend was recorded in the same cropping system by Benjlil et al [99]. Organic matter accumulation in soils causes a significant decrease in nematode abundance [105,106].…”
Section: Effect Of Soil Characteristics On Ppn Abundance In Moroccan supporting
confidence: 63%
“…On the other hand, according to our findings, nitrogen does not appear to have any attraction or depletion effect on nematodes. Benjlil et al [99] indicated that most of the genera identified in saffron (Crocus sativus L.) showed a negative association with total nitrogen (N), which can be explained by the accumulation of nitrate through nitrification that is considered to be harmful to PPNs [100,101]. Similarly, Oteifa [102] showed that the input of nitrogen to the soil had decreased drastically the population of M. incognita in beans crops.…”
Section: Effect Of Soil Characteristics On Ppn Abundance In Moroccan mentioning
confidence: 99%
“…Soil fungal community structure is obvious impacts by the soil physico-chemical properties 7 . Soil pH and enzyme activity are strongly associated with rhizosphere fungal communities as well 8 . Thus, improving the knowledge on soil fungal communities should increase our understanding of their roles in soil ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Soil texture, humidity, rainfall and temperature were the major factors influencing the presence and the population of nematode genera. Ditylenchus, Helicotylenchus and Paratylenchus were reported mainly from the humid and silty soils, whereas the presence of Aphelenchoides, Tylenchus, Tylenchorynchus and Dorylaimus was significantly high in locations with regular rainfall and clay soils [92].…”
Section: Pathogens Associated With Corm Rotmentioning
confidence: 92%
“…Tylenchus, Helicotylenchus, Pratylenchus, Hirschmaniella and Psilenchus are the nematodes genera reported from the saffron fields of Kashmir are [90], and 11 genera have been found in Spain [91]. Aphelenchoides, Ditylenchus, Pratylenchus and Helicotylenchus were reported to parasitize the saffron crop in Morocco [92]. Pratylenchus thornei, Helicotylenchus vulgaris, Aphelenchus avenae, Xiphinema sp., Tylenchus sp., Tylenchorhynchus sp.…”
Section: Pathogens Associated With Corm Rotmentioning
confidence: 99%